Is the threatened land crab Cardisoma guanhumi conquering human-dominated systems? (2024)
ABSTRACT: Land use changes are heralded as a major driver of biodiversity loss. However, recent findings show that cities, perhaps the most radical habitat transformation, sustain increasing numbers of threatened species. This emerging trend has been mostly chronicled for vertebrates from landlocked cities, although loss of biodiversity and rates or urbanization are higher in coastal marine systems. To advance our understanding on how threatened species may conquer human-dominated systems, we studied the threatened edible crab Cardisoma guanhumi and assessed how it is proliferating in croplands and urban systems at different spatial scales and whether populations show consequences of long-term exploitation. We gathered the data on crab populations covering the whole distribution range, including three countries reporting this as a threatened species. The abundance, distribution, and size structure of crab populations among different land uses at local scales were compared and published data for populations thriving in different habitats throughout their distribution range were compiled. We found that at local scale this species is able to thrive in natural and human-disturbed habitats, where food sources are heavily altered. At larger scales, the species showed no differences in abundance and size structure among natural and anthropogenic habitats. In areas near the southern distribution edge, crab populations were more abundant and composed of larger animals in urban areas and croplands than those in natural habitats, suggesting that human-disturbed systems are stepping stones to extend the geographic range. However, we found a long-term reduction in maximum body size, exacerbated by land use changes, that likely reflects exploitation regimes consistently targeting larger crabs. Despite its status as a threatened species, the long history of human exploitation combined with livestock farming practices may explain the proliferation of this crab in human-dominated systems, which emphasize the need to consider conservation in human-dominated systems.